Effects of phosphorus supply levels on the growth and nutrient utilization of Pinus massoniana lamb hybrid saplings - Wang, Wenyue; Hua, Jinguo; Zhang, Zhen; Zhou, Zhichun; Wu, Renchao; Qu, Simin; Chu, Xiuli (Frontiers in Plant Science, 2025)
IntroductionPhosphorus is vital for plant growth but is often limited in subtropical acidic soils, restricting forest productivity. Pinus massoniana, a key timber and resin species in China, shows varied shoot-sprouting characteristics and nutrient use under different phosphorus levels. Understanding its response to fertilization is crucial for optimizing plantation management and growth.MethodsWe employed a two-factor randomized block design with three Pinus massoniana hybrid varieties (with shared male or female parents) and four phosphate fertilizer levels (0, 100, 250, 500 g·plant⁻¹). After three growing seasons, tree height, diameter at breast height (DBH), annual shoot growth characteristics (fixed growth, free growth, shoot number), and growth amount were measured. Nitrogen and phosphorus contents in coniferous leaves were also analyzed.ResultsResults showed significant differences in tree height, DBH, and fixed growth among varieties and fertilizer treatments. The 500 g·plant⁻¹ treatment performed best, with fixed growth 14.35% higher than the control. Free growth and shoot flushing frequency showed no significant differences among treatments. The interaction between variety and fertilization contributed 74.10% to free growth variation. Phosphorus fertilization enhanced growth and nutrient uptake in young Pinus massoniana saplings. Increasing fertilizer intensity raised nitrogen and phosphorus contents and the nitrogen-phosphorus ratio. Correlation analysis revealed that the nutrient environment influences genetic expression among traits, affecting their interrelationships.DiscussionThis study examines how genotype, phosphate fertilizer intensity, and their interaction influence the growth and shoot-sprouting behavior of Pinus massoniana hybrids. Phosphate fertilization is a key driver of early growth and nutrient accumulation, while shoot-sprouting is largely shaped by variety-fertilizer interactions. Findings highlight the need to focus less on the genetic basis of shoot growth and more on how nutrient availability influences variety performance, supporting precise fertilization strategies for optimized forest management.